1
$\begingroup$

This is kind of a reverse question.

A few years back I was presented with a functional equation problem, I don't remember it completely, and now I would appreciate the help of the math.SE hivemind to recreate it.

It concerned a function $f:\Bbb Q^+\to \Bbb Q$, with $\Bbb Q^+$ being the strictly positive rationals. The problem gave two identities for $f$, one of them being $f(x) = f(x^{-1})$. I can't for the life of me recall what the second one was. However, I believe it related $f(x)$ and $f(x+1)$. There is a possibility that $f(1) = 1$ was also included as a restraint.

What I do remember, though, is the solution. With $a, b\in \Bbb Z$ coprime, $f(\frac{a}{b}) = ab$. Also, that the two identities together is in some way related to the Euclidian algorithm.

Long story short, does anyone know what the second identity is / could be?

$\endgroup$
0
$\begingroup$

The 2nd condition can be:

$x \cdot f(x+1) = (x+1) \cdot f(x)$

This gives, $f(m) = m$ for all $m \in \mathbf{Z}$ when used with the fact $f(1) = 1$.

To extend this to positive rationals, we can use $f(x) = f(x^{-1})$ and a repeated use of Euclid's division algorithm (as you mentioned).

$\endgroup$
  • $\begingroup$ This looks like the right one to me. Thanks a lot. $\endgroup$ – Arthur Oct 13 '12 at 9:08
1
$\begingroup$

This has nothing to do with $f(x+1)$, but what about: $$f(x^2)=f(x)^2$$

Edit: what about this one: $$f(x+1)+f(x-1)=2\cdot f(x)$$

$\endgroup$
  • $\begingroup$ $f(x)=0$ and $f(x)=1$ are each solutions for both your suggestions as well as the original $f(x) = f(x^{-1})$ $\endgroup$ – Henry Oct 12 '12 at 19:04
  • $\begingroup$ @Henry if they are identities, they should work for all $x=\frac{a}{b}$ where $a$ and $b$ are coprime. Or am I missing something? $\endgroup$ – Alex Oct 12 '12 at 19:38
  • $\begingroup$ My point was that although $f(\frac{a}{b}) = ab$ is a solution to your expressions (which I upvoted), it is not the only one $\endgroup$ – Henry Oct 12 '12 at 19:46
  • $\begingroup$ @Henry I see what you mean. But how is $f(x)$ a solution for the original identity? (And thanks for the upvote :)) $\endgroup$ – Alex Oct 12 '12 at 19:50
  • $\begingroup$ If $f(x)$ is constant then $f(x) = f(x^{-1})$ $\endgroup$ – Henry Oct 12 '12 at 19:56
0
$\begingroup$

If $a$ and $b$ are coprime then $a+b$ and $b$ are also coprime, so you get $$ f\left(\frac{a}{b} + 1\right) = f\left(\frac{a+b}{b}\right) = (a+b)b = ab+b^2 \text{ if } a,b \text{ coprime} $$ and $$ f\left(\frac{b}{a} + 1\right) = f\left(\frac{b+a}{a}\right) = (b+a)a = ab+a^2 \text{ if } a,b \text{ coprime} $$ and thus generally $$ \frac{f(q^{-1} + 1) - f(q^{-1})}{f(q+1) - f(q)} = q^2 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.